PERTIMBANGAN HAKIM DITOLAKNYA PENGAJUAN JUSTICE COLLABORATOR DALAM TINDAK PIDANA PENYUAPAN (PUTUSAN NOMOR 46/PID.SUS/TPK/2019/PN.Jkt.Pst) - Muhammad Rizqi Andia; Ismawati Septiningsih (Verstek, 2023)
This research aims to analyze and review Judges Legal Considerations regarding the decline of a Justice Collaborator, Arif Fitrawan, in the criminal act of corruption case. How should the Judges' Legal Considerations toward Justice Collaborator on Decision Number 46/Pid.Sus/TPK/2019/PN.Jkt.Pst based on SEMA Number 4 of 2011. This type of research is normative legal research that is perspective and applied with case studies. The technique of collecting primary and secondary legal materials used for this research is documental study and literature materials. The result and discussion indicated that Judges' Legal Considerations (Ratio Decidendi) used to establish the defendant Arif Fitrawan as Justice Collaborator on Decision Number 46/Pid.Sus/TPK/2019/PN.Jkt.Pst, in the writer's opinion it had been appropriate, and according to the criteria for being a Justice Collaborator that regulated on SEMA Number 4 of 2011 and Law Number 13 of 2006 jo. Law Number 31 of 2014 about Protection against Witnesses and Victims. The writer has an opinion that the demands of Public Prosecutor are not overburdening, demands of the Public Prosecutor could referred to as a summary of examination of case based on proofing process. As justice upholders, judges could have a weighting of demands of the Public Prosecutor.Keywords: Criminal Act of Corruption; Justice Collaborator; Ratio Decidendi; Bribery